The introduction of simulation modeling in the Russian hop industry as an innovative digital service for daily consultations of farmers - Afanaseva O. (BIO Web of Conferences)
During the season, the farmer has to make more than 40 different decisions: which seeds to plant, when to plant them, how to process them, how to treat a diseased plant and others, how to cope with adverse weather conditions, which ones and when to expect certain natural phenomena threatening crops. The crop industry remains particularly sensitive to these factors, as product collections are highly dependent on weather conditions. At the same time, about 70% of the loss factors, including those caused by adverse weather conditions, can now be controlled using digital services and ensuring the availability of consulting services for farmers. Simulation modeling in hop farming is such a solution. The model created by us allows hop growers to quickly and efficiently calculate the economic results of their decisions and the validity of their investments. Various situations can be modeled, thanks to which preventive management decisions are made and the level of risks is calculated under various changeable external operating conditions, whether it is spikes in energy prices, plant protection products, planting material, etc. The main effective parameters of the model are indicators of profitability of hop cultivation and return on capital investments. This functionality allows to use a simulation model when planning a business, when choosing optimal solutions for extensive or intensive hop farming development.